From Leisure to Study: On the Cultivation and Transmission of an Art - López, Maximiliano (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
In the pages to follow, I propose a meditation on the concept of study, its place in our contemporary scene, and its relation to the classical notion of leisure. In general terms, we can define leisure as an extreme disposition or state in which our relation to the world remains indeterminate in some way. In this sense, leisure favours a radical experience of the open and ungraspable characteristics of the human world. This is a nearly intolerable state. Reactions against it tend toward work, diversion, entertainment, or consumption. The hypothesis that I wish to explore in this essay, then, is the idea that study consists, in a singular and properly school-related manner, in inhabiting leisure, a condition which today deserves to be cultivated and protected. This idea of study is a way of being and dwelling in which the existence of a common world is in play and at stake.